(untitled) (Economic Journal of Nepal, 2015)
This study aims to analyze the government expenditure under major headings and tries to establish the relationship of government expenditure with GDP. Regression equations are estimated to find the causal relationship of government expenditure with GDP. Cointegration estimation is detected to find the long run equilibrium stability, and error correction model is estimated for short term analysis. It is noticed that the share of government capital expenditure is on decreasing trend mainly after 1990s. The share of economic services expenditure is also on decreasing trend with the rapid increase in government expenditure on loan repayment and interest payment. The finding of this research supports the findings of earlier researcher in the sense that the government expenditure is growth promoting. However, there is not satisfactory contribution of government expenditure to GDP. The cointegration relationship of GDP has appeared with recurrent expenditure, gross investment and labour force (with and without). The error correction model is also positively significant that the increase in recurrent expenditure and gross investment cause positively to GDP even in short run. This study underscores the importance of government expenditure and suggests for efficiently on its reallocation. The Economic Journal of Nepal Vol. 35, No. 4, October-December 2012 (Issue N0. 140) Page: 215-234